The IDP and infrastructure service delivery challenges in Dihlabeng local municipality. - Lemako, Johannes (My University, 2014)
ABSTRACT In South Africa, the government’s process of transformation which effectively started in 1994 not only resulted in a new democracy, a new government or dispensation, but it also championed a significant, rapid and radical transformation of local government in South Africa, as well as a radical transformation of municipal planning. The South African municipal planning system, in spite of various efforts and policy developments made over time, is still struggling to adapt to, and implement, the new principles that apply and is not addressing the development goals in all parts of the country effectively. This research recognises the IDP as an important planning tool that can potentially address service delivery challenges inherited from the apartheid regime and in particular infrastructure service delivery challenges within the Dihlabeng Local Municipality. However, for the IDP to achieve its mandated goals, an enabling institutional culture within the Dihlabeng Local Municipality as well as a performance management system must be implemented and monitored accordingly. Municipal planning needs to be developmentally oriented, and a municipality must undertake developmentally-oriented planning so as to ensure that it strives to achieve the objectives of local government as set out in section 152 of the Constitution and gives effect to its developmental duties as required by section 153 of the Constitution. This research presents an interrogation of the IDP in Dihlabeng Local Municipality and its impact in addressing infrastructure service delivery challenges facing this municipality as well as an attempt to present some propositions to address these shortcomings. This research revealed that IDP planning does take place at Dihlabeng Local Municipality, and that proper processes were followed in producing the IDP. It was established, however, that farming communities were not included in this process and that this actually made it difficult for the municipality’s IDP to impact in these communities. It was also discovered that the infrastructure service delivery challenges experienced in urban communities were mainly due to poor maintenance of the existing infrastructure, ageing infrastructure and shortages of qualified maintenance personnel.
MM 2014
Keywords: Local government, Municipal services,Public administration.